Municipalities as Educational Producers - An Efficiency Approach - Staffan Waldo (Lund University, School of Economics and Management, Department of Economics, 2001)
This paper studies efficiency in the provision of public education by local authorities using Data Envelopment Analysis (DEA). Viewing education as a multilevel production process the models control for differences at other levels. Most important is the students' socioeconomic backgound and a number of alternative ways of modelling this are proposed. Mean efficiency is estimated to between 0.87 and 0.96. To explain the efficiency we use the estimated scores as dependent variable in a Tobit regression. The primary findings are that municipalities with a socialistic majority in the city council are less efficient, that the share of teachers having a permanent tenure increases efficiency significantly which empasize the importance of employment contracts and, contrary to our expectations, that municipalities with many pedagogially skilled teachers are less efficient. We find no evidence of efficiency increases due to competition from private schools.
Keywords: I21; 330; DEA; municipality; education; school